The re-emergence and transmission of Monkeypox virus in Nigeria: the role of one health - Ogunleye, Seto C.; Akinsulie, Olalekan C.; Aborode, Abdullahi T.; Olorunshola, Mercy M.; Gbore, Damilola; Oladoye, Moyinoluwa; Adesola, Ridwan O.; Gbadegoye, Joy O.; Olatoye, Boluwatife J.; Lawal, Mariam A.; Bakare, Akeem B.; Adekanye, Oluwabori; et al. (Frontiers in Public Health, 2024)
The Monkeypox virus, commonly abbreviated as mpox, is a viral zoonosis that is experiencing a resurgence in prevalence. It is endemic to regions of West and Central Africa that are characterized by dense forested areas. Various measures pertaining to animals, humans, and the environment have been recognized as potential factors and catalysts for the spread of the disease throughout the impacted regions of Africa. This study examines the various factors contributing to the transmission of the virus in Nigeria, with a particular focus on the animal-human and inter-human modes of transmission in rural communities and healthcare facilities. The One Health approach was emphasized as crucial in the prevention and management of this issue. Literature suggests that preventing repeated zoonotic introductions could potentially halt the transmission of the mpox virus from animal to human hosts, leading to a potential decrease in human infections.